The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1080/07317115.2015.1101632
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Functional Vulnerability Predicts Fraud Cases in Older Adults: Results of a Longitudinal Study

Abstract: Using cross sectional data Psychological vulnerability was identified as a correlate of older adult’s being defrauded. We extend that research by examining fraud prevalence using longitudinal data from the Health and Retirement Study, and to identify the best predictors of fraud longitudinally across a 4-year time frame. Whereas reported fraud prevalence was 5.0% in a 5-year look-back period in 2008, it increased to 6.1% in 2012. The rate of new-incident fraud across only a 4-year look-back was 4.3%. Being you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 19 publications
(18 reference statements)
3
50
1
Order By: Relevance
“…For example, these include the Older Adult Financial Exploitation Measure (Conrad et al 2010), and the Lichtenberg Financial Decision Screening Scale (LFDSS) which provide tools for assessing financial decision making and preventing financial exploitation. Although such tools need rigorous testing, they may be a further means of supporting professionals who seek to disrupt financial scammers whilst supporting those who fall prey to them (Lichtenberg, Ficker et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For example, these include the Older Adult Financial Exploitation Measure (Conrad et al 2010), and the Lichtenberg Financial Decision Screening Scale (LFDSS) which provide tools for assessing financial decision making and preventing financial exploitation. Although such tools need rigorous testing, they may be a further means of supporting professionals who seek to disrupt financial scammers whilst supporting those who fall prey to them (Lichtenberg, Ficker et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Some previous survey-based studies showed that older adults were not more likely to fall for fraud than young adults (Lichtenberg et al 2016;Ross et al 2014;Sugiura 2013;Wood et al 2015). However, these findings referred to more general forms of fraud (e.g., "Have you been the victim of financial fraud in the past five years (Yes, No)?…”
Section: Introductionmentioning
confidence: 93%
“…Lichtenberg and colleagues sampling of a largely African-American population found self-reported financial exploitation to be 18% when using an 18-month look back period (Lichtenberg et al, 2015a). Using the Psychosocial Leave Behind Questionnaire (Smith et al, 2013); a sub-study of the large population based Health and Retirement study Lichtenberg et al (2016) examined the prevalence of fraud in older adults. Among older adults, the overall reported prevalence of fraud across a 5-year look back increased significantly between 2008 and 2012: from 5.0% (347 out of 6,920) to 6.1% (442 out of 7,253), for a 22% increase.…”
Section: Significance Of the Issuementioning
confidence: 99%